Scaling effect on the detachment of pressure-sensitive adhesives through fibrillation characterized by a probe-tack test. Issue 28 (29th June 2020) - Takahashi, Kosuke; Oda, Ryuto; Inaba, Kazuaki; Kishimoto, Kikuo
Abstract : Scaling effect of adhesion force at detachment was clarified by a probe-tack test using a glass sphere at mm-scale and an AFM cantilever. Abstract : This study extensively investigates the fibrillation process of a pressure-sensitive adhesive (PSA) using a probe-tack test. It was conducted using a glass sphere at the millimeter scale for various thicknesses of PSA layers laminated on a glass substrate, on various contact areas. A sharp decrease in the adhesion force caused by cavity growth was confirmed in the case of large contact areas, whereas cavities were not generated in the case of small contact areas on the thick PSA layer. Furthermore, an atomic force microscopy (AFM) cantilever was used to conduct a probe-tack test on considerably smaller contact areas at the micrometer scale, to focus on the fibrillation process by avoiding the cavity-growth. The transition of the adhesion force during the release process by the AFM cantilever was confirmed to resemble the transition in the fibrillation process obtained using the glass sphere by the repeated tests using the probe without cleaning the surface. The fully adhesive failure was also confirmed by the tests at sufficiently high release velocity. A comparison of these tests at different scales revealed that the detachment force from the probe at the millimeter scale is proportional to the contact area, and determined using the release-strain rate through elongation of the entire thickness of the PSA layer. By contrast, the detachment force from the AFM cantilever is proportional to the contact radius and determined using the release velocity regardless of the PSA thickness.